Formulation rationale for the development of SARS-COV-2 immunochromatography rapid test kits in India - Prince Manta, Raveen Chauhan, Himanshu Gandhi, Shikha Mahant, Deepak N. Kapoor (Journal of Applied Pharmaceutical Science, 2021)
Humanity has been continuously threatened by epidemics and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has shown greater epidemic potential. According to the World Health Organization, measures such as rapid diagnosis, immediate isolation, and precautionary contact tracing are key tools of epidemic control. The method of detection or testing is critical in this epidemiological control, where SARS-CoV-2-positive cases are increasingly growing, leading to community infection. Immunochromatographic test kits have been described for the diagnosis of various infectious diseases because of their rapid scalability, convenient use, and prompt validation. The benefits of the immunochromatographic test kits include evaluation of the sample in approximately 20 minutes, lower cost per sample, and simple directions to use. Such test kits are composed of an uncut sheet structure that is protein conjugated, labeled with markers, and reagents coated in a nitrocellulose membrane. The need for thorough vetting is a major concern for the Central Drugs Standard Control Organization, Indian Council of Medical Research and other regulators, as more businesses are rushing to produce serologic test kits for SARS-CoV-2 worldwide. Initial reports of 86%−89% sensitivity and 84.2%–98.6% specificity were reported for these kits. Nonetheless, many national reports show variability in test accuracy significantly among various commercial suppliers. The virus's more recent mutated strains (B.1.1.7, B.1.617, and B.1.351) have also raised concerns about their detectability using these test kits. In India, manufacturers are developing rapid test kits to detect SARS-CoV-2 by importing pre-antigen or antibody-coated uncut sheets from vendors and then cutting them into strips. Such sheets also have problems with specificity and are expensive. The possibility of developing kits with an indigenous protein coating and conjugation to detect antigens and antibodies needs to be explored by Indian researchers. This communication describes techniques to develop precise rapid test kits for detecting SARS-CoV-2.
Keywords: Corona antigen, corona antibodies, COVID-19, lateral flow test, point- of care, SARS-COV-2